2008
DOI: 10.1029/2008pa001613
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the glacial ocean to Heinrich events from different iceberg sources, as modeled by a coupled atmosphere‐iceberg‐ocean model

Abstract: [1] We introduce explicit icebergs from a dynamic and thermodynamic iceberg model into an intermediate complexity climate model, which includes the coupled atmosphere-ocean system. This modeling approach allows iceberg meltwater to be injected into the ocean on the basis of thermodynamical considerations along the iceberg trajectories. Icebergs are seeded from known ice sheets in both hemispheres. Adding icebergs to the present-day climate model has a minimal impact, but during the Last Glacial Maximum (LGM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(163 citation statements)
references
References 82 publications
(88 reference statements)
11
147
2
Order By: Relevance
“…After the iceberg/freshwater release ends in year 300, MOC recovery shows a delay of up to 5 decades when comparing hosing with the CF-icebergs. This is quite consistent with the idea (Jongma et al 2009;Levine and Bigg 2008) that hosing is too efficient at shutting down convection. The less convection remains active, the larger the build up of fresh surface waters in the Eastern North Atlantic Ocean (Figs.…”
Section: Peak-response: Delayed Moc Recoverysupporting
confidence: 79%
See 2 more Smart Citations
“…After the iceberg/freshwater release ends in year 300, MOC recovery shows a delay of up to 5 decades when comparing hosing with the CF-icebergs. This is quite consistent with the idea (Jongma et al 2009;Levine and Bigg 2008) that hosing is too efficient at shutting down convection. The less convection remains active, the larger the build up of fresh surface waters in the Eastern North Atlantic Ocean (Figs.…”
Section: Peak-response: Delayed Moc Recoverysupporting
confidence: 79%
“…• Compared to traditional homogeneous fresh-water hosing, Cool & Fresh-icebergs are almost as efficient as hosing at weakening the meridional overturning circulation, even though hosing can be regarded as an in principle too-efficient manner to suppress convection (Jongma et al 2009;Levine and Bigg 2008).…”
Section: Synthesis and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, they showed that, contrary to Levine and Bigg (2008) and Jongma et al (2009), icebergs were much more efficient at suppressing deep convection when the latent heat is taken into account. This counter-intuitive result (cooling the surface ocean should generate denser waters) is explained by a 'sea-ice facilitation effect', whereby the cooling effect of icebergs promotes sea-ice formation.…”
Section: Modelling the Impact Of Iceberg And Meltwater Events On The mentioning
confidence: 99%
“…As such, recent thermo-dynamical iceberg models have been coupled to climate models. One of the first studies to undertake this approach was Levine and Bigg (2008), who accounted for both the distribution of icebergs and their freshwater release. With icebergs, they found a greater freshwater release is required to have the same effect on the AMOC than the traditional freshwater hosing approach.…”
Section: Modelling the Impact Of Iceberg And Meltwater Events On The mentioning
confidence: 99%